2021
DOI: 10.1177/0268355521996087
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of blood flow in the internal jugular vein with the use of computational fluid mechanics software

Abstract: Objectives To determine the site and nature of altered hemodynamics in pathological internal jugular veins. Method With the use of computational fluid mechanics software we simulated blood flow in 3 D models of the internal jugular veins that exhibited different morphologies, including nozzle-like strictures in their upper parts and valves in the lower parts. Results In a majority of models with nozzle-like strictures, especially those positioned asymmetrically, abnormal flow pattern was revealed, with signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
4
7
0
Order By: Relevance
“…This study confirmed the results of our previous study [ 25 ], which was based on a different computational fluid mechanics (CFM) package. Similar to the findings of this research, we demonstrated that stenosis located at the beginning of the internal jugular vein can significantly affect the blood flow pattern.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study confirmed the results of our previous study [ 25 ], which was based on a different computational fluid mechanics (CFM) package. Similar to the findings of this research, we demonstrated that stenosis located at the beginning of the internal jugular vein can significantly affect the blood flow pattern.…”
Section: Discussionsupporting
confidence: 91%
“…This in silico study is the continuation of that research [ 25 ] and was aimed at understanding the influence of stenoses located at the beginning of IJV on the flow through this vein and the functioning of the jugular valve located downstream.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative interpretation of flow disturbances in these veins is that the main source of abnormal outflow are nozzlelike strictures in their upper parts, at the level or just below the jugular foramen, for example, caused by an enlarged transverse process of the atlas and/or styloid process of the temporal bone. 1 These in silico studies were aimed at validation of this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Perhaps, this complication in this unique venous territory occurs in patients with anatomical variants of the cerebral veins and sinuses, which evokes venous stasis in the cerebral circulation in the decubitus body position (in the upright body position a substantial part of blood flows out of the cranial cavity through the vertebral venous pathway, thus should not be affected, even is a case of anatomical anomalies). 22 , 23 An activation of neutrophils in the settings of blood stasis is a well-known phenomenon. 24 However, if such a pathomechanism was actually playing a role, immunothrombotic occlusions could also occur in other veins with stagnant flow, such as varicose veins.…”
mentioning
confidence: 99%